Infants Recognize the Subtle Happiness Expression. (April 2014) - Ichikawa, Hiroko; Kanazawa, So; Yamaguchi, Masami K
Facial movement facilitates the recognition of facial expressions. While an intense expression is expressive enough to be recognized in a still image, a subtle expression can be recognized only in motion (Ambadar, Schooler, & Cohn, 2005, Psychological Science, 16, 403–410). The present study investigated whether infants recognize a subtle expression, and whether facial movement facilitates infants' recognition of a subtle expression. In experiment 1 4- to 7-month-old infants were tested for their spontaneous preference for a happy subtle expression rather than a neutral face, but they did not show a spontaneous preference. To confirm that infants did not recognize the static subtle expression, we conducted experiment 2 using the familiarization-novelty procedure. Infants were first familiarized with a static subtle happy expression. Following familiarization, they were presented with a pair of peak expressions of happiness and anger, but showed no significant novelty preference. In experiment 3 we presented the subtle expression dynamically. Infants were familiarized with a dynamic subtle expression and were tested for their novelty preference. The 6- to 7-month-olds showed a significant novelty preference, while 4- to 5-month-olds did not. These results suggest that infants can recognize the subtle expression only in dynamic presentation and that facial movement facilitates infants' recognition of facial expression.